Vertical Integration or Disintegration? A Bargaining Model of the Maquiladora's Case - Ikuho Kochi; Ramsés Jiménez Castañeda; Raúl Alberto Ponce Rodríguez (Nóesis)
In this paper we present an analytical framework to study the demands of foreign and domestic factors of production of the maquiladora industry. We derive the net profitability of demanding high in72 9 Vol. 21 ¿ número 41 ¿ 2012 stead of low quality inputs. We argue that differences in the quality of inputs between foreign and domestic factors can explain the low vertical integration of the maquiladora with the Mexican industry. We show that if the difference in quality and its positive effect in marginal production compensates the difference in prices, then the maquiladora can be induced to integrate vertically with foreign suppliers of inputs, even if the unitary cost to demand foreign inputs is strictly higher than that of domestic inputs. We also show that a depreciation of the Mexican exchange rate does not necessarily increase the maquiladora's demand of Mexican inputs. This explains recent empirical evidence showing this phenomenon. Conversely, a depreciation of the exchange rate might increase the maquiladora's demand of imported inputs if foreign and domestic factors are complementary. The above holds even if the domestic supplier participates in a bargaining game offering an efficient contract.